Peningkatan Pengetahuan dan Persepsi terhadap Penyakit Demam Berdarah Dengue pada Santri di Pondok Pesantren dengan Metode Ceramah Edukasi - Tri Baskoro Tunggul Satoto; Dwiputro, Alfin Harjuno (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
Dengue hemorrhagic fever (DHF) is a vector-borne disease which posses a great threat for public health sector in many countries, including Indonesia. It is estimated more than 390 million cases are reported annually worldwide. Indonesia is one of the countries with the highest number of dengue cases in the world, with 95,000 cases recorded in 2018. Vector control is the main strategy for preventing the transmission of Dengue infection. Vector control practices are influenced by the level of public knowledge and perception. This study aimed to determine and improve the level of knowledge and perceptions of Islamic boarding school students regarding DHF transmission. This was a quasi-experimental research with one group pretest & posttest. The interventions carried out were in the form of health promotion with educational lectures on the prevention and transmission of DHF. The level of knowledge and perception was measured before and after the intervention using a questionnaire. The number of respondents in this study were 166 respondents, with most of them are female (50.6%). There was an increase in the average posttest scores compared to the pretest with respective averages of 63.84 ± 12.02 and 75.74 ± 11.78 (p = 0.0001). The existence of health promotion in the santri group could increase knowledge and perception of DHF as a vector-borne disease.